Comparison Between Zinc Sulphate with Mefenamic Acid versus Mefenamic Acid Alone in the Management of Primary Dysmenorrhea - Nayab Amir, Rabia Wajid, Sadaf Zahra, Maria Ishtiaq, Samia Riaz, Safia Liaqat, Kiren Khurshid Malik, (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To evaluate the efficacy of the zinc sulfate plus mefenamic acid versus mefenamic acid alone on the severity of pain score in patients with primary dysmenorrhea using WaLIDD and Wong Baker score. Methods: This clinical experimental trial was conducted at Department of Gynecology, Lady Willingdon Hospital Lahore from 1st July 2022 to 30th June 2023 over a period of 12 months and 72 patients were enrolled. They were divided into 2 groups by random allocation. In Group A patients were given zinc sulphate (20mg) plus mefenamic acid (500 mg) andmefenamic acid (500 mg)only in Group B. The WaLIDD and Wong Baker score was used to measure the severity of dysmenorrhea, which ranged from 0 to 12. Patients were evaluated for pain using a visual analog score (VAS). Follow-up was done for three menstruation cycles. Results: The mean ages were 24.36±3.60 years in group A and 24.00±3.76 years in group B respectively. There were 23 (63.9%) in group A and 28 (77.8%) in group B women presented with moderate dysmenorrhea while 13 (36.1%) women in group A and 8 (22.2%) women in group B presented with severe dysmenorrhea. At 1st month and 2nd month no significant difference was seen for pain score between groups. At 3rd months mean pain score in group A was 3.38 and in group B was 3.93 which was statistically significant difference (p=0.016). At 1st and 2nd month pain score showed no significant difference between groups. However, at 3rd month 21 (58.33%) women in group A and 12 (33.3%) women in group B had mild pain while 16(44.4%) women in group A and 24(66.7%) women in group B had moderate pain. At 3rd month pain status showed significant difference between groups. Women in group A had better pain control as compared to group B patients. Conclusion: The addition of zinc supplementation to mefenamic acid is more effective as compared to mefenemic acid alone for treating pain in primary dysmenorrhea patients. Keywords: Primary dysmenorrhea, Pain, Efficacy, Zinc sulfate, Mefenamic acid